Frederick Douglass, a Psychobiography Rethinking Subjectivity in the Western Experiment of Democracy - Gibson, Danjuma G. (Black Religion/Womanist Thought/Social Justice, 2018)
In the extreme context of the American slavocracy, how do we account for the robust subjectivity and agency of Frederick Douglass? In an environment of extremity, where most contemporary psychological theory suggests the human spirit would be vanquished, how did Frederick Douglass emerge to become one of the most prolific thinkers of the 19th century? To address this question, this book engages in a psychoanalytic examination of all four of Frederick Douglass' autobiographies. Danjuma Gibson examines when, how, and why Douglass tells his story in the manner he does, how his story shifts and takes shape with each successive autobiography, and the resulting psychodynamic, pastoral, and practical theological implications.